2018
DOI: 10.4103/0974-7796.164843
|View full text |Cite
|
Sign up to set email alerts
|

Increased burden on metropolitan urological services: The era of the Australian National Emergency Access Targets (NEAT or the “4-h target”)

Abstract: Background:The National Emergency Access Targets (NEAT) was introduced in Australia in 2011 and guides the clearance of presentations within 4-h of initial presentation from the Emergency Department (ED). We aim to assess the impact of the introduction of NEAT on acute urological services at a large metropolitan center.Methods:A retrospective cohort study was performed and data were collected from electronic patient management systems. The control group was represented by ED presentations between June and Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…An Australian study on NEAT targets conducted by urologists in Western Australia yielded similar results, with only a modest reduction in ED LOS and no improvement in time to theatre. They noted an increase in inappropriate referrals and an increase in inter‐unit transfer of undifferentiated patients who did not require specialist input 11 . No hospital in Australia has consistently met NEAT targets >85% 12 and clinicians need to be wary that standardized triage and referral targets do not compromise their patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Australian study on NEAT targets conducted by urologists in Western Australia yielded similar results, with only a modest reduction in ED LOS and no improvement in time to theatre. They noted an increase in inappropriate referrals and an increase in inter‐unit transfer of undifferentiated patients who did not require specialist input 11 . No hospital in Australia has consistently met NEAT targets >85% 12 and clinicians need to be wary that standardized triage and referral targets do not compromise their patient care.…”
Section: Discussionmentioning
confidence: 99%
“…They noted an increase in inappropriate referrals and an increase in inter‐unit transfer of undifferentiated patients who did not require specialist input. 11 No hospital in Australia has consistently met NEAT targets >85% 12 and clinicians need to be wary that standardized triage and referral targets do not compromise their patient care.…”
Section: Discussionmentioning
confidence: 99%
“…General surgery's elective activities within traditional models of care were particularly prone to interruption, due to caring for more than twice as many emergency patients as any other surgical specialty [ 31 ]. Local forces such as governmental targets to limit patient time in the emergency department have also incentivized surgical staff allocation to emergency patients [ 32 , 33 ]. Additionally, there are more general surgeons than any other type [ 34 ], providing capacity to dedicate separate personnel in the ASU model.…”
Section: Discussionmentioning
confidence: 99%
“…National Emergency Access Targets (NEAT) reinforce the pressure for the timely flow of patients through the ED. NEAT was introduced in Australia in 2011 to reduce ED wait times and improve the quality of patient care after studies showed the impaired flow of emergency admissions could adversely affect patient outcomes (Perera et al., 2018; Shetty et al., 2017). These targets contribute to the pressure on nursing staff to view patient flow as the priority rather than seeing the whole patient, taking into consideration their needs and preferences.…”
Section: Discussionmentioning
confidence: 99%